Antinociceptive effects of methadone combined with detomidine or acepromazine in horses - Lopes, C. [UNESP]; Luna, S. P. L. [UNESP]; Rosa, A. C. [UNESP]; Quarterone, C. [UNESP]; Crosignani, N. [UNESP]; Taylor, P. M.; Pantoja, J. C. [UNESP]; Puoli, J. N. P. [UNESP] (EVJ Ltd., 2015)
To investigate two protocols to provide antinociception in horses. To evaluate the antinociceptive effects of intravenous methadone combined with detomidine or acepromazine in adult horses. Randomised, blinded, crossover study. Mechanical, thermal and electrical stimuli were applied to the dorsal left and right metacarpus and coronary band of the left thoracic limb, respectively. A thermal stimulus was applied caudal to the withers. The horses were treated with saline (C), a combination of methadone (0.2 mg/kg bwt) and detomidine (10 μg/kg bwt) (MD) or methadone (0.2 mg/kg bwt) and acepromazine (0.05 mg/kg bwt) (MA) at 1 week intervals. Nociceptive thresholds were measured before and at 15 min intervals until 150 min after treatment. Wilcoxon rank-sum and Wilcoxon signed rank tests were used to compare data between groups at each time point and over time within each group, followed by the Bonferroni method to adjust the P value. The mechanical stimulus was the most sensitive test to differentiate the antinociceptive effects of the treatments. Mechanical thresholds were greater after MD than MA between 15 and 30 min and with both MD and MA these thresholds were greater than C from 15 to 60 min. Electrical and thermal limb thresholds were greater after MD than C at 15 and 45 min and at 15, 30, 45, 75 and 105 min, respectively. Thermal limb thresholds were greater with MA than C at 30 min. Thoracic thermal threshold in MD and MA were higher than C at 45, 75, 90 and 120 min and from 30 to 75 min, respectively. Methadone and acepromazine produced less pronounced mechanical antinociception than MD.
Keywords: Analgesia; Electrical stimulus; Horse; Mechanical stimulus; Thermal stimulus